Inoculação de salmonella enterica subespecie enterica sorovar enteritidis fagotipo 4 em ovos embrionados de duas linhagens de frango de corte - Andradae, Maria Auxiliadora (2005)
Two experiments were carried out to evaluate the use of quaternary ammonia on Salmonella Enteritidis inoculated in eggshell and its penetration capacities, verify the ability to infect the egg inoculated in eggshell, determine embryo mortality, infect hatched chicks and affect incubation parameters of two broiler lines. A total of 302 and 290 fertile eggs of Ross and ISA Label, respectively, were distributed in six treatments: eggs sanitized with placebo (Treatment 1- PC) quaternary ammonia inoculated with Salmonella Enteritidis (Treatment 2-PI); eggs non-sanitized and inoculated placebo (Treatment 3- NPC) with Salmonella Enteritidis (Treatment 4- NPI); eggs inoculated in allantoidal cavity with placebo (Treatment 5-CAC) or Salmonella Enteritidis (Treatment 6- CAI). Immediately after inoculation, the eggs were hatched and embryo mortality was evaluated after 96, 432 and 528 hours. The qualitative results were analyzed by non-parametric tests of chi-square and Kruskall-Wallis. The incubation parameters were not affected when the pathogen was inoculated in eggshell. It was observed that Salmonella Enteritidis inoculated in allantoidal cavity determined late embryo mortality in fast 17,02% and slow growing 13,04% lines, and eggs inoculated in allantoidal cavity originated chicks with high frequency of intestinal colonization by Salmonella Enteritidis of 76,67% and 26,67% Ross and ISA Label, respective.